Pengaruh Kualitas Produk Makanan terhadap Loyalitas Pelanggan (Suatu Kajian Teoritis) - Setyopratignyo, Raden Mas Listijono (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study discusses the influence of food product quality on customer satisfaction and loyalty. The method used is a literature review with a narrative overview approach. The result of this study is that there is a significant influence between the quality of food products and customer satisfaction. The higher the quality of the food products offered, the more satisfied customers will be. But this is not the case with the influence between customer satisfaction and loyalty. There are other factors that also have a strong influence on customer loyalty, namely trust, commitment, and emotional bonding.